METODE OUTDOOR LEARNING TERHADAP KEMAMPUAN MENGENAL WARNA PADA ANAK TUNAGRAHITA RINGAN - Angraeni, Riski (Jurnal Pendidikan Khusus, 2017)
Abstract : This research is based on the understanding of the development of the ability to recognize color in children with mild mental retardation as the main obstacle, so it is necessary to be given learning using outdoor learning method. The purpose of this study is to prove the effect of outdoor learning methods on the ability to recognize the color in children with mild mental retardation. The research method used is quantitative approach of pre-experimental type and design of one-group pretest-posttest design.The subjects used were six mild mental retardation students in grade 3 of elementary school in SitiHajarSpecial Education School of Sidoarjo. Technique of collecting data in the form of test, observation, and documentation.While the technique of data analysis using non parametric statistic with test formula Wilcoxon Match Pairs Test. The results showed that Zcounted = 2.20 is greater than Ztable = 1.96 with a 5% crisis value which means that the method of outdoor learning has been shown to influence the ability to recognize color in children with mild mental retardation of grade 3 of elementary school in Siti Hajar Special Education School of Sidoarjo.   Keywords : recognize color, outdoor learning